Anton, a Special-Purpose Machine for Molecular Dynamics Simulation. - Shaw, David E.; Deneroff, Martin M.; Dror, Ron O.; Kuskin, Jeffrey S.; Larson, Richard H.; Salmon, John K.; Young, Cliff; Batson, Brannon; Bowers, Kevin J.; Chao, Jack C.; Eastwood, Michael P.; Gagliardo, Joseph; et al. (Communications of the ACM, 2008)
The ability to perform long, accurate molecular dynamics (MD) simulations involving proteins and other biological macro-molecules could in principle provide answers to some of the most important currently outstanding questions in the fields of biology, chemistry, and medicine. A wide range of biologically interesting phenomena, however, occur over timescales on the order of a millisecond—several orders of magnitude beyond the duration of the longest current MD simulations. We describe a massively parallel machine called Anton, which should be capable of executing millisecond-scale classical MD simulations of such biomolecular systems. The machine, which is scheduled for completion by the end of 2008, is based on 512 identical MD-specific ASICs that interact in a tightly coupled manner using a specialized high-speed communication network. Anton has been designed to use both novel parallel algorithms and special-purpose logic to dramatically accelerate those calculations that dominate the time required for a typical MD simulation. The remainder of the simulation algorithm is executed by a programmable portion of each chip that achieves a substantial degree of parallelism while preserving the flexibility necessary to accommodate anticipated advances in physical models and simulation methods.